CASE OF NON-SEVERE CONGENITAL NEPHROTIC SYNDROME - I. S. Kostushina; T. V. Margieva; T. N. Gusarova; G. T. Yakhyaeva; L. S. Namazova-Baranova; A. A. Pushkov; K. V. Savost'yanov (Педиатрическая фармакология, 2014)
Nephrotic syndrome is a severe renal disease that may result in the end-stage renal failure despite the extent of proteinuria. Prognosis and tactics of therapy of nephrotic syndrome depend both on the morphological diagnosis and on the cause of the disease. It ought to be considered that congenital nephrotic syndrome is resistant to immunosuppressive therapy. However, several foreign authors demonstrate cases of immunosuppressive therapy effectiveness (steroids and cyclosporine A) in a range of familial cases of nephroticsyndrome. Timely detection of children with genetically caused nephrotic syndrome allows to define the patient management tactics in each case on time. This clinical case represents non-severe course of congenital nephrotic syndrome caused by an NPHS2 gene mutation, which had not before been described neither in Russian nor in foreign literature. The authors deem introduction of the molecular genetic analysis to the routine clinical practice for all cases of congenital nephrotic syndrome and steroid-resistant nephrotic syndrome reasonable.